3b+5b=2(2-b)+6(b-2)

Simple and best practice solution for 3b+5b=2(2-b)+6(b-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3b+5b=2(2-b)+6(b-2) equation:


3b+5b=2(2-b)+6(b-2)

We simplify the equation to the form, which is simple to understand
3b+5b=2(2-b)+6(b-2)

Reorder the terms in parentheses
3b+5b=+(+4-2b)+6*(b-2)

Remove unnecessary parentheses
+3b+5b=+4-2b+6+*(+b-2+)

Reorder the terms in parentheses
3b+5b=+4-2b+(+6b-12)

Remove unnecessary parentheses
+3b+5b=+4-2b+6b-12

We move all terms containing b to the left and all other terms to the right.
+3b+5b+2b-6b=+4-12

We simplify left and right side of the equation.
+4b=-8

We divide both sides of the equation by 4 to get b.
b=-2

See similar equations:

| 3x-24=2x+35 | | 1.4x-0.9=33 | | (10x+29)= | | 5(y+4)=-8y-45 | | 6+2=14-x | | 315+15p=450 | | 8x-6-3x=4 | | -x+3y-4z=-15 | | 200p+40p=350+50p | | 14=n+2 | | 6-4t=10 | | 180=4y+(x+2y) | | x=-2y+5z-9 | | t^2+4t-1=t^2+2t+2 | | -2x^2+8x-9=0 | | 2(2k^2+81)-k= | | y=x^3-6x^2+9x+15 | | -1+4x=14+13x | | -4-2x=-5x-16 | | -x^2+4x+32=32 | | 2t+5-6t= | | 5a^2-4a-12= | | 27a=80.73 | | -29-j=0 | | 7a-3=-2a | | x^2-1x+7=49 | | 39.2=-4.9x^2+29.4x+0 | | 4x+18=2x+12 | | 3(x+2y)=2x+5y | | 3(x+2y)=2x+y | | -5x+20=1+x | | -2500+-200x=12 |

Equations solver categories